FORMATION OF PROFESSIONAL AND PERSONAL LEVEL OF PSYCHOLOGY TEACHER - Перепелюк, Т. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
Different aspects of formation and development of professional skills of professor, his individuality during professional activity, self-education and self-development are examined in the article. Key words: professor of psychology, professional capabilities, skills, personal qualities.